STUDI KELAS KESESUAIAN LAHAN TANAMANTEBU LAHAN KERING SEBAGAI DASAR PENGELOLAANNYA DI KEC. KEMLAGl KAB. MOJOKERTO - -, Siswanto; Sutrisno, Hadi (MAPETA, 2000)
Study onrainfed sugarcane land suitability clasification  as a basis for farm management The land studied was grouped into five mapping  units (SPK I, SPK II, SPK III, SPK IV and SPK V), bases on degree of production. The result showed that all actual sub classes of SPK were relatively uniform, including S3 (Marginal suitable) with drainage, available  P, and Total N as limiting factors .. These  should  be  overcame  by organic  matter,  Phosphat  and  Nitrogen  fertilizers  application  and  drainage management